Dependence of Parallel Electrical Conductivity in the Topside Ionosphere on Solar and Geomagnetic Activity. Issue 6 (3rd June 2021) - Giannattasio, F.; Pignalberi, A.; De Michelis, P.; Coco, I.; Consolini, G.; Pezzopane, M.; Tozzi, R.
Abstract: The spatial and temporal dynamics of ionospheric currents are among the most evident manifestations of the interaction between the magnetized plasma of solar origin and the magnetosphere‐ionosphere system. In this context, a special role is played by field‐aligned currents (FACs), which drive energy and momentum exchanges between the magnetosphere and the ionosphere, deeply affecting the energy balance of the latter. One of the most relevant physical quantities that may help to fully characterize FACs is the ionospheric electrical conductivity. Understanding the features associated with this quantity may contribute to the advancement of knowledge on the mechanisms of solar wind‐magnetosphere‐ionosphere interaction as well as energy storage and dissipation involved in the space weather phenomena. By extending a previous study, we investigate the dependence of the electrical conductivity parallel to the geomagnetic field on solar and geomagnetic activity. To this aim, we considered a six‐year long data set of in‐situ electron density and temperature values recorded by the Langmuir probes on board the Swarm satellites in the topside ionosphere. With this large data set, we computed global maps of the parallel electron conductivity under both quiet and disturbed conditions, and for different solar activity levels. In both cases, the International Reference Ionosphere (IRI) model allowed estimating the contribution of particle precipitation to electrical conductivity. Key Points: Analysis of the parallel electrical conductivity in the topside ionosphere by using 6 years of in‐situ Swarm A measurements is performed The dependence of the parallel electrical conductivity on both solar and geomagnetic activity is investigated The comparison with the IRI model allowed estimating the contribution to the parallel conductivity mainly due to particle precipitations